Mature cystic teratoma of renal pelvis: An unusual presentation at an uncommon site - Bhuvanagiri Srihari Balaji; Immanuel Sampath Karl (Wolters Kluwer Medknow Publications, 2019)
Teratoma of the kidney is uncommon. We report a case of a young boy with a large, right-sided retroperitoneal cyst suspected as lymphangioma causing hydronephrosis. His renal pelvis was dilated, containing purulent fluid, and a nephrectomy was performed. Histopathology revealed a mature cystic teratoma of the renal pelvis.